Efficient identification protocol provably secure in standard model - LI Yan-ping1; WANG Yu-min1 (Tongxin xuebao)
Based on the hardness assumption of the collusion attack algorithm with k traitors （K-CAA） in a gap Diffie-Hellman （GDH） group, a new and efficient identification protocol is proposed. The new identification protocol is proven secure against impersonation under concurrent reset attack setting in standard model. Due to its simplicity and naturalness, low-memory, low-computation costs, and better security, the proposed scheme is well suitable for using in computationally limited devices for identification such as smart cards.